The potential role and mechanism of Rhizoma Coptidis in prevention of diabetic encephalopathy: targeting sodium ion and channels - Cao, Ning; Shou, Zhangxuan; Wang, Mimi; Wu, You; Wang, Xuefeng (Frontiers in Pharmacology, 2025)
IntroductionRhizoma Coptidis (RC) is an edible and medicinal herb with anti-hyperglycemia, which has potential application in the prevention of diabetic encephalopathy (DE). However, its efficacy and underlying mechanism in DE prevention have not been elucidated yet. The objective of the current study is to investigate the preventive effect of RC on DE, thereby focusing on the target through the method of network pharmacology and molecular docking.MethodsSixty 4-week-old, male C57BL/6 mice were randomly allocated to six groups: control, model, metformin (200 mg/kg), RCL (0.75 g/kg), RCM (1.5 g/kg), and RCH (3 g/kg). The DE-model mice were induced by streptozocin combined with a high-fat diet. In addition, the neuroprotective effect of RC was determined both in vivo and in vitro. Network pharmacology analysis was used to screen the potential mechanism of RC. Thereafter, the underlying mechanism of action of RC was explored by molecular docking prediction and Western blot analysis. An analysis of patients with DE was performed to validate it from another perspective.ResultsThe results showed that the cognitive state of DE model mice was improved and neuronal injury was ameliorated after RC administration. Active compounds in RC, berberine and coptisine, were found to ameliorate HT22 injury induced by high glucose. Network pharmacology results suggest that voltage-gated sodium channel subtypes (Nav1.1, Nav1.2, and Nav1.6) may be the targets for RC prevention of DE. Furthermore, the Western blot analysis revealed that RC significantly upregulated Nav1.1 and Nav1.2, while Nav1.6 could not. In addition, serum sodium was related to the cognitive status of DE patients, which can be used as a diagnostic index for mild and moderate–severe DE.DiscussionRC has the potential to be a functional food or adjuvant drug for DE prevention, and Nav1.1 and Nav1.2 are promising DE intervention targets.